Oceanographic parameters associated with spatial occurrence of cephalopods in standardized demersal fishing trawls in the NE Atlantic - Daniel Oesterwind; Anne Marie Power; Esther Abad; Gregoire Certain; Nikolaos Fotiadis; Alexey Golikov; Ángel F. González; Vladimir Laptikhovsky; Silvia S. Monteiro; Carlos Montero-Castaño; Ana Moreno; Hassan Moustahfid; et al. (Marine Biology, 2026)
In this work, the environmental occurrence ranges of different European cephalopod species are described for the whole NE Atlantic shelf including the greater North Sea and Baltic Sea. This is done based on the environmental parameters collected in-situ during surveys that caught commercially important cephalopod species (1990–2022). Results are supplemented and compared with information available in the published literature and are discussed in relation to available habitat across the range, survey design, etc., and, in particular, which species are most likely to be affected by climate change. Our analyses illustrate that Loligo forbesii occupies a broader depth range than Loligo vulgaris and Alloteuthis spp. Because L. forbesii occurs further offshore and at greater depths, this species is likely more resilient to warming than the other loliginids in our study. Octopus vulgaris is documented in areas close to the coast with a more southerly distribution, whereas Eledone cirrhosa occurs further north and further away from the coast. Eledone cirrhosa occurs at lower temperatures and has a much broader depth range, which may provide resilience against warming. By contrast, both ommastrephid squid species ( Illex coindetii and Todaropsis eblanae ) showed a very similar tolerance to the three environmental variables (salinity, temperature, depth). This information should contribute to future species distribution modelling by allowing validation of realistic results against each species’ range, habitat requirements, and environmental ranges, while appreciating the data limitations caused by the timing and gear used in the survey cruises that supply occurrence and density data.

Large-scale carbon storage in the deep-sea through cold-water coral mounds off the Campeche Bank, Gulf of Mexico - L. Greiffenhagen; J. Titschack; C. Wienberg; L. H. De Clippele; L. Matos; J. Gafeira; A. Schröder-Ritzrau; K. Arul; N. Frank; D. Hebbeln (Coral Reefs, 2026)
Reef-building cold-water corals form large seabed structures known as coral mounds. As demonstrated in studies from the Northeast Atlantic and Mediterranean Sea, coral mounds accumulate large amounts of carbon(ate). However, beyond the scale of individual mounds, long-term accumulation of both organic (C org ) and inorganic carbon (C inorg ) at the mound province scale remains poorly quantified. In this study, we investigate the Campeche Mound Province, southern Gulf of Mexico, which consists of interconnected coral mound ridges covering an area of > 40 km 2 . Using sediment cores, we reconstruct total carbon (C org and C inorg ) accumulation in the Campeche Mounds over the past ~ 250 kyr. The results show mean total carbon accumulation rates of 0.5–5.6 g C cm −2 kyr −1 . This is three to nine times higher than on the surrounding seafloor. We then upscale obtained carbon concentration data to the entire mound province using high-resolution bathymetry and the CoMMa toolbox, a novel morphometric mapping tool. The total carbon storage of the Campeche Mounds amounts to an estimated 18.5 megatons of carbon that is transferred to the long-term carbon cycle and immobilised for millions of years. For the first time, we present a combination of core-based analysis and spatial mapping. Through accounting for different approaches and time scales, we provide reliable value ranges for carbon accumulation rates in coral mounds. The Campeche Mound Province is not fully mapped and likely much larger, highlighting the substantial, albeit overlooked long-term carbon burial through benthic deep-sea ecosystems in the southern Gulf of Mexico and beyond.

Nanoplastics influence on toxic metal bioaccumulation and antioxidant responses in Lactuca sativa L. irrigated with treated wastewater - A.M. Barreiros; H.F. Silva; L. Araújo; J. Coelho; C.M. Oliveira; N. Silva; M. Matos; S. Piçarra (Science of The Total Environment, 2026)

Circularity strategies for steel in the EU: Insights from consolidated material flows data - L. Ciacci; J. Fellner; C.T. Matos; T. Maury; F. Mathieux (Resources, Conservation and Recycling, 2026)

Concrete Jungle: habitat heterogeneity acts as environmental filter on multidimensional diversity of fruit-feeding butterflies in urban Savannahs of Cerrado biome - Geraldo de Brito Freire; Israel Pereira dos Santos Ribeiro; Ana Carolina Lacerda de Matos; Sofia Coradini Schirmer; Eduardo Guimarães Santos; Fernanda Vieira da Costa; Felipe M. Gawryszewski; Lee A. Dyer; Onildo J. Marini-Filho; Pedro Togni (Urban Ecosystems, 2026)

Unveiling the Hidden Biotechnological Potential of the Vermetid Gastropod Vermetus triquetrus: Insights into an Unexplored Marine Resource - A. Breves; C. Cardoso; C. Afonso; J. Matos; J. Lobo-Arteaga; C. Bartilotti; S. Sales; S. Pedro; N. M. Bandarra (Marine Biotechnology, 2026)
The vermetid Vermetus triquetrus , commonly found on intertidal hard substrates in the Mediterranean Sea and the Portuguese coast, remains an underexplored marine resource. This study aimed to determine the total polyphenol content, fatty acid (FA) composition, and biological activity (antioxidant and anti-inflammatory properties) in the visceral mass and the head-foot part of this sessile gastropod from a population collected in Mira Estuary, mainland Portugal. The FA profile of the visceral mass albeit rich in saturated FA had significant levels of long-chain polyunsaturated FA, arachidonic acid (20:4 ω6), 6.3%, and eicosapentaenoic acid (20:5 ω3, EPA), 4.2% of total FA, and a non-negligible content of docosapentaenoic (22:5 ω3), 2.1%. Moreover, though the FA profile of the head-foot part was not attained, regarding other parameters, there were differences between the visceral mass and head-foot part of V. triquetrus. In fact, concerning polyphenol content, whereas the head-foot contained a total of 142 ± 14 mg GAE/100 g dw, the visceral mass reached a high level of 314 ± 90 mg GAE/100 g dw. The antioxidant activity as measured by FRAP showed a similar pattern of higher values in the visceral mass than in the head-foot, 55.6 ± 18.3 µmol Fe2+/g dw vs. 9.8 ± 0.8 µmol Fe2+/g dw. Finally, the ABTS methodology largely agreed with polyphenol levels and FRAP, being the head-foot with 1189 ± 223 µmol Trolox Eq/100 g dw less antioxidant than the visceral mass, 5511 ± 2304 µmol Trolox Eq/100 g dw. Given the presence of anti-inflammatory compounds, such as polyphenols (more abundant in the visceral mass), anti-inflammatory activity, as measured by COX-2 inhibition %, was detected, reaching more than 30% in the visceral mass. Therefore, the gastropod V . triquetrus can be a source of polyphenolic compounds, being specially its visceral mass, not only a rich source of polyphenols, but also a starting material for highly antioxidant extracts. Given the known biological activity of polyphenols and the convergence of results with the FRAP and ABTS antioxidant activity methods, further study on the specific phenolic composition and extract fractionation and refining is warranted.

Native Trichoderma spp. as biocontrol agents against common beans anthracnose - S. C. Izidoro-Morimitsu; A. Knob; C. K. Matos; C. M. D. R. Faria; J. Kawakami (Journal of Plant Diseases and Protection, 2026)

Experimental evidence of ciliate dispersal and successional patterns via endozoochory in temporary aquatic systems - Crislaine Cochak; Andy J. Green; Marta I. Sánchez; Alfonso Pineda; Matheus Henrique de Oliveira de Matos; Luiz Felipe Machado Velho (Protist, 2026)

Prospection of Autochthonous Lactic Acid Bacteria Displaying Probiotic Potential to Enhance Colossoma macropomum Larvae Growth and Immunoprotection Against Aeromonas hydrophila - Thayná M. dos Santos; Layana A. B. Pereira; Laine P. C. dos Santos; Andrya L. Lopes; Larissa A. F. Sampaio; Graziella V. G. de Matos Silva; Juliana N. Ferreira; Gleika T. J. Dos Reis; Jonny B. Teixeira; Raimundo J. T. Diniz‐Neto; Laura G. M. de Carvalho; Michelle Midori Sena Fugimura; et al. (Journal of Fish Diseases, 2026)
This study assessed the functional potential of autochthonous lactic acid bacteria isolated from the gastrointestinal tract of tambaqui ( Colossoma macropomum ) as larviculture probiotics. Five strains were selected and identified as belonging to the genus Weissella . In vitro assays revealed high tolerance to acidic pH (2.0–3.0), resistance to bile salts (10%), biofilm formation capacity, hydrophobicity and direct Aeromonas hydrophila inhibition. In in vivo tests, strains M13 and M14 promoted significant increases in tambaqui survival (72.2% and 68.7%; p

Project Psyche: reference genomes for all Lepidoptera in Europe - Charlotte J. Wright; Niklas Wahlberg; Roger Vila; Marko Mutanen; Pável Matos-Maraví; Kay Lucek; Irena Kleckova; Leonardo Dapporto; Vlad Dincă; Claudia Bruschini; Christopher W. Wheat; Marta Vila; et al. (Trends in Ecology & Evolution, 2025)

Geochemistry of the volcano-sedimentary complex of the Algarve Basin (Silves-Ayamonte, SW Iberia) - A. Díez-Montes; R. Solá; J. J. Huerta; S. Machado; R. Dias; J. X. Matos; M. López (Journal of Iberian Geology, 2025)
The Volcano-Sedimentary Complex of the Algarve basin (south of the Iberian Peninsula) belongs to the Large Igneous Province of the Central Atlantic Magmatic Province (CAMP), which developed c.200 Ma following the start of the breakup of Pangaea, and preceding the opening of the Atlantic Ocean. This volcanic complex was emplaced in a short period of time in the Lower Jurassic (Hettangian-Sinemurian). It includes subaerial lava flows, pyroclastic deposits and peperites, and contemporaneous sedimentation. We present new field evidence and geochemical data of mafic rock suites within a > 150 km long transect across the volcanic belt. The rocks have a subalkaline geochemical affinity and low TiO 2 contents. They are moderately evolved (Mg# 53–76) and have quartz-hypersthene-normative associations, classifying as low-Ti tholeiites (TiO 2 = 1.2–1.5 wt%). They have slight yet variable enrichment in light ion lithophile and light rare erath elements [(La/Yb) N = 2.55–3.40] and a negative Ta-Nb anomalies. The mafic rocks have enriched MORB compositions, compatible with low-Ti tholeiitic CAMP suites. A trait of CAMP basaltic flows is their compositional homogeneity. Distinct volcanic rocks are only described in the Algarve basin, and have relatively lower SiO 2 and high CaO contents than typical CAMP rocks. Our data suggest that the subset of volcanic rocks with lower SiO 2 and high CaO are linked to contamination-assimilation of ascending magmas with carbonate-evaporite material from Silves marl-carbonated-evaporitic complex, immediately underlying the CAMP sequences.

Bovine and ovine deltapapillomavirus coinfection associated with equine sarcoid - E. L. Pereira; G. R. Pereira; M. L. de Osório; J. L. A. Terra; J. B. Gayger; J. S. Gularte; M. Demoliner; V. M. A. G. Pereira; M. Filippi; Q. S. de Matos; A. Tessman; C. W. Canal; et al. (Brazilian Journal of Microbiology, 2025)

Here, There and Everywhere: Widespread Non‐Native Plants in the World's Urban Ecosystems - David M. Richardson; Lauren B. Trotta; Myla F. J. Aronson; Benjamin Baiser; Marc W. Cadotte; Marta Carboni; Laura Celesti‐Grapow; Sonja Knapp; Ingolf Kühn; Ana Carolina Lacerda de Matos; Zdeňka Lososová; Daijiang Li; et al. (Global Ecology and Biogeography, 2025)
Aim To (a) produce a list of the most widespread naturalised non‐native plant species across cities of the world; (b) explore whether cities on different continents are invaded by the same group of widespread naturalised species; and (c) elucidate the origins of the most widespread naturalised urban species. Location Global. Time Period No specific period. Major Taxa Studied Vascular plants. Method Using the most comprehensive and up‐to‐date dataset of non‐native urban floras yet assembled (GUBIC; Global Urban Biological Invasions Compendium), we identified the most widespread naturalised plant species (the global urban florome) by filtering for taxa present across all continents (except Antarctica) and their frequency in urban areas. To assess global patterns of urban plant naturalisation, we conducted ordination analyses and visualised species co‐occurrence. We also examined species origins and their environmental impact. Results Among the 7792 naturalised plant species recorded in 553 urban centres, 302 species (4%) were found on all six continents. Of these, 96 species, considered the most widespread species, were present in more than half of urban centres in Oceania, North America and South America; this proportion was higher than in Africa, Asia and Europe. Cities outside Europe and Asia are more homogeneous in terms of the species composition of the most widespread invaders. An analysis of species origins showed that temperate Asia contributed the most species globally, while intercontinental exchange patterns varied, with a notable one‐directional flow from North to South America. Main Conclusions Our results suggest that urban ecosystems outside Europe and Asia are more susceptible to recent invasions than those within these two continents. Understanding the composition and origins of these widespread species is crucial for developing coordinated management strategies and improving the resilience of urban biodiversity.

Addressing Critical Fungal Pathogens Under a One Health Perspective: Key Insights from the Portuguese Association of Medical Mycology - R. Sabino; F. Antunes; R. Araujo; A. R. Bezerra; J. Brandão; C. Carneiro; A. Carvalho; D. Carvalho; I. C. Conceição; F. Cota Medeiros; C. Cruz; E. Duarte; et al. (Mycopathologia, 2025)
Fungal infections have emerged as a significant public health concern, especially with the increasing incidence of severe mycoses caused by pathogens such as Aspergillus fumigatus , Candida auris , Candida albicans , and Cryptococcus neoformans . These fungi, listed as critical priorities by the World Health Organization, pose a heightened risk due to rising antifungal resistance and their severe impact on immunocompromised individuals. This article, coordinated by the Portuguese Association of Medical Mycology, highlights the importance of adopting a One Health perspective to address fungal threats comprehensively. Drawing on interdisciplinary collaboration, the association aims to foster greater awareness, improve diagnostic capabilities, and stimulate research and public health policies in Portugal but also at global level. The paper outlines key strategies for surveillance, prevention, and innovation in fungal diagnostics and therapeutics. Moreover, it emphasizes the urgent need for national coordination and international cooperation in managing fungal infections, advocating for integrative approaches that link human, animal, and environmental health. By presenting a consolidated overview of current challenges and future priorities, this work seeks to enhance preparedness and response mechanisms in the face of escalating fungal threats.

Mathematical modeling of multicomponent extraction of metal ions by polymer membranes - M. B. de Vilhena; B. C. de Matos Junior; J. L. Ferreira; S. de A. Cardoso; B. M. Viegas; J. N. N. Quaresma; J. A. da S. Souza; E. N. Macêdo (International Journal of Environmental Science and Technology, 2025)

Neurological lesions in cervids: A study in Portugal - M.A. Pires; J. Macêdo; F. Seixas; A. Gama; M. de Lurdes Pinto; A. Alves; I. Pires; A. Cristina Matos; L. Figueira; C. Lima; P. Mendonça; P. Carvalho; et al. (Journal of Comparative Pathology, 2025)

Enhancing commercial SOFCs fed directly with ethanol through a modified manganite coating - F. Matos de Oliveira; S. Vecino-Mantilla; Z. Hafsi; M.V. Barp; F. D’Acapito; A. Puri; J. Perez; E. Ticianelli; M. Lo Faro (Chemical Engineering Journal, 2025)

Corrigendum to “Synthesis of controlled size starch nanoparticles (SNPs) title of article” [Carbohydr. Polym. 250 (2020) 116938] - G. Gutiérrez; D. Morán; A. Marefati; J. Purhagen; M. Rayner; M. Matos (Carbohydrate Polymers, 2025)

Insights into the thermal stability properties of two hardwoods from the Amazon rainforest - L. de Souza-Cavalcante; F. Guerrero; J. Anglada-Rivera; Y. Leyet; F. M. A. da Silva; G. Q. Ramos; R. Matos; H. D. da Fonseca Filho (Journal of the Indian Academy of Wood Science, 2025)

Do (xeno)estrogens pose a risk to earthworms? Soy isoflavones and estradiol impact gonad structure and induce oxidative stress in Eisenia fetida - Tiago Azevedo; Rita Silva-Reis; Beatriz Medeiros-Fonseca; Mariana Gonçalves; Gabriel Mendes; Marta Roboredo; Maria J. Rocha; Francisco Peixoto; Maria de Lurdes Pinto; Manuela Matos; João R. Sousa; Paula A. Oliveira; et al. (Chemosphere, 2025)

The importance of tropical tree-ring chronologies for global change research - Peter Groenendijk; Flurin Babst; Valerie Trouet; Ze-Xin Fan; Daniela Granato-Souza; Giuliano Maselli Locosselli; Mulugeta Mokria; Shankar Panthi; Nathsuda Pumijumnong; Abrham Abiyu; Rodolfo Acuña-Soto; Eduardo Adenesky-Filho; et al. (Quaternary Science Reviews, 2025)

Around the World in 26 Million Years: Diversification and Biogeography of Pantropical Grass‐Yellow Eurema Butterflies (Pieridae: Coliadinae) - Jing V. Leong; Pável Matos‐Maraví; Rayner Núñez; Renato Nunes; Weijun Liang; Michael F. Braby; Tenzing Doleck; Kwaku Aduse‐Poku; Yutaka Inayoshi; Yu‐Feng Hsu; Niklas Wahlberg; Djunijanti Peggie; et al. (Journal of Biogeography, 2025)
Aim Grass‐yellow butterflies ( Eurema ) are a group of pantropical Pieridae distributed throughout Asia, Australasia, Africa and the New World. However, little is known about their diversification, including the biogeographic mechanism(s) explaining their circumglobal distribution. We present the first densely sampled, time‐calibrated phylogeny and biogeographic reconstruction of grass‐yellows to confirm the monophyly of the genera, re‐evaluate their taxonomy and infer the biogeographic events contributing to their worldwide distribution. Location Global tropics and subtropics. Taxon The butterfly tribe Euremini (Pieridae: Coliadinae). Methods We analysed up to 391 genetic loci from 126 samples of 66 ingroup species. Divergence dating was accomplished in a Bayesian phylogenetic framework using secondary calibration points, and maximum likelihood models of various biogeographic models were fitted to the data using the R package BioGeoBEARS. We used the best fitting model to estimate relative dispersal events with biogeographical stochastic mapping. Finally, we estimated branch‐specific speciation and extinction rates to assess the diversification history of the group. Results Different phylogenomic analyses converged on similar topologies with robust support. Grass‐yellows emerged ca . 26 Mya in the New World, and a single extant lineage dispersed to Asia in the early Miocene, where they diversified and dispersed to Africa and Australasia. The fastest rates of diversification occurred in the Old World tropics during the late Miocene. Many of the grass‐yellow genera were either paraphyletic or polyphyletic as traditionally circumscribed. To maintain nomenclatural stability, we place all grass‐yellows in Eurema sensu lato and recognise two subgenera: Eurema ( Abaeis ) and Eurema ( Eurema ). Main Conclusions Grass‐yellow butterflies originated in the Americas and attained their global distributional patterns via dispersal. The Indo‐Australian and Caribbean archipelagoes seem to have accelerated the diversification of the group, and movement in and out of these island regions was frequent. Although the traditional view of founder‐event speciation envisions migrants from large landmasses (‘mainland’) colonising smaller landmasses (‘islands’), we find that island to mainland dispersal and differentiation were equally or more common.

Enhancing orofacial pain relief: α-phellandrene complexed with hydroxypropyl-β-cyclodextrin mitigates orofacial nociception in rodents - Brennda Gonzaga Machado; Fabíolla Rocha Santos Passos; Ângelo Roberto Antoniolli; Erik W. Menezes Pereira; Tiffany Karoline Barroso Santos; Brenda Souza Monteiro; Pollyana de Souza Siqueira Lima; Saulo Santos Matos; Marcelo Cavalcante Duarte; Adriano Antunes de Souza Araújo; Jackson Roberto Guedes da Silva Almeida; Raimundo Gonçalves Oliveira Júnior; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Steam reforming for winery wastewater treatment: Hydrogen production and energy self-sufficiency assessment - J. Matos; M.A. Soria; Luis M. Madeira (Biomass and Bioenergy, 2025)

The potential of the water-energy-food nexus approach in advancing the sustainable development goals: A PRISMA-based systematic review - Glorynel Ojeda-Matos; J. Leah Jones-Crank (Environmental Science & Policy, 2025)

Reaction of two sciaenid species to passing boats: Insights from passive acoustic localisation - André B. Matos; Manuel Vieira; M. Clara P. Amorim; Paulo J. Fonseca (Estuarine, Coastal and Shelf Science, 2024)

Unsupervised segmentation for sandstone thin section image analysis - Rayan T. C. M. Barbosa; E. L. Faria; Matheus Klatt; Thais C. Silva; Juliana. M. Coelho; Thais F. Matos; Bernardo C. C. Santos; J. L. Gonzalez; Clécio R. Bom; Márcio P. de Albuquerque; Marcelo P. de Albuquerque (Computational Geosciences, 2024)

Supplementation with 25-hydroxicolecalciferol increases the nutritional efficiency and carcass growth of grazing Nellore young bulls - Fernanda S. Mudado; Melissa B. Silveira; Henrique J. Fernandes; Alexandre Perdigão; Diego M.M. dos Santos; Thomas H.R. da Silva; Jarbas M. da Silva Júnior; Isabelle E. de Matos; Victor V. de Carvalho; Tiago S. Acedo; Aline G. da Silva (Animal Feed Science and Technology, 2024)

Left atrial fractional shortening in cats: a comparison between two echocardiographic views - A. Machado; C. Partington; J. Silva; L. Gardner; J. Novo Matos (Journal of Veterinary Cardiology, 2024)

Soil carbon stock changes in a crop-livestock-forestry integration in Southern Goiás State, Brazil - B. E. Madari; P. S. Matos; J. M. Oliveira; M. T. M. Carvalho; A. L. R. Silveira; P. L. O. A. Machado; W. A. Araujo; M. M. B. Siqueira; T. M. Ferraresi; F. M. C. Freitas; P. V. Rizzo; R. R. Silva; et al. (Agroforestry Systems, 2024)

Fisheries and the COVID-19 pandemic: A global scoping review of the early pressures, impacts, and responses in least developed, emerging, and developed countries - Richard A. Nyiawung; Taylor Ehrlick; Nathan J. Bennett; Nicolas D. Brunet; Fabio Matos; Cristina Pita; Joshua S. Stoll; Philip A. Loring (Regional Studies in Marine Science, 2024)

Clinical signs associated with severe ST segment elevation in three cats with a hypertrophic cardiomyopathy phenotype - J. Seo; T.A. Kurosawa; K. Borgeat; J. Novo Matos; J.C. Hutchinson; O.J. Arthurs; V. Luis Fuentes (Journal of Veterinary Cardiology, 2024)

Geography and ecology shape the phylogenetic composition of Amazonian tree communities - Bruno Garcia Luize; David Bauman; Hans ter Steege; Clarisse Palma‐Silva; Iêda Leão do Amaral; Luiz de Souza Coelho; Francisca Dionízia de Almeida Matos; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Florian Wittmann; Carolina V. Castilho; Marcelo de Jesus Veiga Carim; et al. (Journal of Biogeography, 2024)
Aim Amazonia hosts more tree species from numerous evolutionary lineages, both young and ancient, than any other biogeographic region. Previous studies have shown that tree lineages colonized multiple edaphic environments and dispersed widely across Amazonia, leading to a hypothesis, which we test, that lineages should not be strongly associated with either geographic regions or edaphic forest types. Location Amazonia. Taxon Angiosperms (Magnoliids; Monocots; Eudicots). Methods Data for the abundance of 5082 tree species in 1989 plots were combined with a mega‐phylogeny. We applied evolutionary ordination to assess how phylogenetic composition varies across Amazonia. We used variation partitioning and Moran's eigenvector maps (MEM) to test and quantify the separate and joint contributions of spatial and environmental variables to explain the phylogenetic composition of plots. We tested the indicator value of lineages for geographic regions and edaphic forest types and mapped associations onto the phylogeny. Results In the terra firme and várzea forest types, the phylogenetic composition varies by geographic region, but the igapó and white‐sand forest types retain a unique evolutionary signature regardless of region. Overall, we find that soil chemistry, climate and topography explain 24% of the variation in phylogenetic composition, with 79% of that variation being spatially structured ( R 2 = 19% overall for combined spatial/environmental effects). The phylogenetic composition also shows substantial spatial patterns not related to the environmental variables we quantified ( R 2 = 28%). A greater number of lineages were significant indicators of geographic regions than forest types. Main Conclusion Numerous tree lineages, including some ancient ones (>66 Ma), show strong associations with geographic regions and edaphic forest types of Amazonia. This shows that specialization in specific edaphic environments has played a long‐standing role in the evolutionary assembly of Amazonian forests. Furthermore, many lineages, even those that have dispersed across Amazonia, dominate within a specific region, likely because of phylogenetically conserved niches for environmental conditions that are prevalent within regions.

Antimicrobial resistance patterns of Staphylococcus spp. isolated from clinical specimens of companion animals in Northern Portugal, 2021–2023 - D. Araújo; R. Oliveira; B.L. Silva; J. Castro; C. Ramos; F. Matos; C. Almeida; S. Silva (The Veterinary Journal, 2024)

Phosphate buffering in mangrove sediment pore water under eutrophication and deforestation influences - Grazielle Nascimento-Silva; Gabriela B. Oliveira; Christiene R.L. Matos; Edouard Metzger; Christian J. Sanders; Humberto Marotta; Rut Díaz; Gwenaël Abril; Wilson Machado (Marine Pollution Bulletin, 2024)

The decline and death of Canary Island date palms in México City is associated with subgroup 16SrIV-D phytoplasmas - C. F. Ortiz-García; D. Alvarado-Rosales; C. Oropeza; L. de L. Saavedra-Romero; S. Aranda-Ocampo; A. Almaraz-Sánchez; A. Quezada-Salinas; A. Equihua-Martínez; S. E. García-Díaz; M. Narváez; G. Nic-Matos; P. J. Palma-Cancino; et al. (Australasian Plant Pathology, 2024)

Chemical prospection and antioxidant activity of Humiria balsamifera (Aubl.) A. St. Hil. AND Hymenaea courbaril L. - Jhuliana Monteiro de Matos; Andressa Rose Castro Costa; Marciel Nascimento Justino; Marcos Bispo Pinheiro Camara; Osmar Luis Silva Vasconcelos; J. C. Marques; Clenilma Marques Brandão; Georgiana Eurides de Carvalho Marques (Natural Product Research, 2024)

Two- and three-dimensional transesophageal echocardiographic assessment and successful occlusion of a window-like patent ductus arteriosus in two dogs - I. Craciun; J. Silva; L.C. Dutton; J. Loureiro; J. Novo Matos (Journal of Veterinary Cardiology, 2024)

Hypertrophic cardiomyopathy in a dog: a systematic diagnostic approach - J. Novo Matos; J. Silva; S. Regada; S. Rizzo; M. Serena Beato; C. Basso (Journal of Veterinary Cardiology, 2024)

Isolated discrete upper septal thickening in a non-referral cat population of senior and young cats - J. Novo Matos; J.R. Payne; J. Mullins; V. Luis Fuentes (Journal of Veterinary Cardiology, 2023)

An improved reference genome and first organelle genomes of Quercus suber - Ana Usié; Octávio Serra; Pedro M. Barros; Pedro Barbosa; Célia Leão; Tiago Capote; Tânia Almeida; Leandra Rodrigues; Isabel Carrasquinho; Joana B. Guimarães; Diogo Mendoça; Filomena Nóbrega; et al. (Tree Genetics & Genomes, 2023)
Cork oak ( Quercus suber L.) is an ecologically and economically important evergreen tree species native to the Mediterranean region and widespread in southwest Europe and northwest Africa. An improved genome assembly of cork oak using a combination of Illumina and PacBio sequencing is presented in this study. The assembled genome contains 2351 scaffolds longer than 1000 bp, accounting for 765.7 Mbp of genome size, L90 of 755, and a N50 of 1.0 Mbp, with 40,131 annotated genes. The repetitive sequences constitute 53.6% of the genome. The genome sequences of chloroplast and mitochondrion were determined for the first time, with a genome size of 161,179 bp and 531,858 bp, respectively. Phylogenetic analysis based on complete chloroplast genome sequence showed that Q. suber is closely related to Quercus variabilis , two cork-producing species with commercial use. All data generated are available through the public databases, being ready to be used without restrictions. This study provides an improved nuclear genome assembly together with the organelle genomes of cork oak. These resources will be useful for further breeding strategies and conservation programs and for comparative genomic studies in oak species.

Predictors for Prolonged Hospital Stay Solely to Complete Intravenous Antifungal Treatment in Patients with Candidemia: Results from the ECMM Candida III Multinational European Observational Cohort Study - Matthias Egger; Jon Salmanton-García; Aleksandra Barac; Jean-Pierre Gangneux; Hélène Guegan; Valentina Arsic-Arsenijevic; Tadeja Matos; Rok Tomazin; Nikolai Klimko; Matteo Bassetti; Helena Hammarström; Eelco F. J. Meijer; et al. (Mycopathologia, 2023)
Background To date, azoles represent the only viable option for oral treatment of invasive Candida infections, while rates of azole resistance among non-albicans Candida spp. continue to increase. The objective of this sub-analysis of the European multicenter observational cohort study Candida III was to describe demographical and clinical characteristics of the cohort requiring prolonged hospitalization solely to complete intravenous (iv) antifungal treatment (AF Tx). Methods Each participating hospital (number of eligible hospitals per country determined by population size) included the first ~ 10 blood culture proven adult candidemia cases occurring consecutively after July 1st, 2018, and treating physicians answered the question on whether hospital stay was prolonged only for completion of intravenous antifungal therapy. Descriptive analyses as well as binary logistic regression was used to assess for predictors of prolonged hospitalization solely to complete iv AF Tx. Findings Hospital stay was prolonged solely for the completion of iv AF Tx in 16% (100/621) of candidemia cases by a median of 16 days (IQR 8 – 28). In the multivariable model, initial echinocandin treatment was a positive predictor for prolonged hospitalization to complete iv AF Tx (aOR 2.87, 95% CI 1.55 – 5.32, p < 0.001), while (i) neutropenia, (ii) intensive care unit admission, (iii) catheter related candidemia, (iv) total parenteral nutrition, and (v) C. parapsilosis as causative pathogen were found to be negative predictors (aOR 0.22 – 0.45; p < 0.03). Interpretation Hospital stays were prolonged due to need of iv AF Tx in 16% of patients with candidemia. Those patients were more likely to receive echinocandins as initial treatment and were less severely ill and less likely infected with C. parapsilosis .

P23-05: Urinary monohydroxyl-polycyclic aromatic hydrocarbons and metals in firefighters with active participation in controlled structure fires - J. Teixeira; R. Azevedo; A. Almeida; F. Rodrigues; A. Santos-Silva; C. Delerue-Matos; M. Oliveira (Toxicology Letters, 2023)

P16-13: A step forward the in vitro toxicity assessment of firefighters’ exposure to controlled fires in human cell culture models - M.J. Bessa; J. Teixeira; C. Delerue-Matos; B. Sarmento; M. Oliveira; F. Rodrigues (Toxicology Letters, 2023)

Time-space evolution of Iberian Pyrite Belt igneous activity: Volcanic and plutonic lineaments, geochronology, ore horizons and stratigraphic constraints - Luís Albardeiro; Igor Morais; João X. Matos; Rita Solá; Rute Salgueiro; Zélia Pereira; Márcia Mendes; Maria J. Batista; Daniel de Oliveira; Alejandro Díez-Montes; Carlos Inverno; Nelson Pacheco; et al. (Gondwana Research, 2023)

Exploring the prevalence and antibiotic resistance profile of Klebsiella pneumoniae and Klebsiella oxytoca isolated from clinically ill companion animals from North of Portugal - D. Araújo; J. Castro; F. Matos; R. Oliveira; C. Ramos; C. Almeida; S. Silva (Research in Veterinary Science, 2023)

Ventricular pre-excitation in cats: 17 cases - M. Sidler; G. Santarelli; A. Kovacevic; J. Novo Matos; N. Schreiber; M. Baron Toaldo (Journal of Veterinary Cardiology, 2023)

The phylogenomics and evolutionary dynamics of the organellar genomes in carnivorous Utricularia and Genlisea species (Lentibulariaceae) - Saura R. Silva; Vitor F.O. Miranda; Todd P. Michael; Bartosz J. Płachno; Ramon G. Matos; Lubomir Adamec; Sergei L.K. Pond; Alexander G. Lucaci; Daniel G. Pinheiro; Alessandro M. Varani (Molecular Phylogenetics and Evolution, 2023)

Thin and hypokinetic myocardial segments in cats with cardiomyopathy - J. Novo Matos; J. Sargent; J. Silva; J.R. Payne; J. Seo; I. Spalla; K. Borgeat; J. Loureiro; N. Pereira; I.C. Simcock; J.C. Hutchinson; O.J. Arthurs; et al. (Journal of Veterinary Cardiology, 2023)

Impact of anthropogenic noise on the survival and development of meagre (Argyrosomus regius) early life stages - Rita Trabulo; M. Clara P. Amorim; Paulo J. Fonseca; Manuel Vieira; André B. Matos; Thibaut Marin-Cudraz; Marco F.L. Lemos; Ariana B. Moutinho; Sara C. Novais; Pedro Pousão-Ferreira; Ana Candeias-Mendes; Ana M. Faria (Marine Environmental Research, 2023)

A model of distributed parameters for non-Fickian diffusion in grain drying based on the fractional calculus approach - Gustavo S. Matias; Fernando H. Lermen; Camila Matos; Douglas J. Nicolin; Clovis Fischer; Diogo F. Rossoni; Luis M.M. Jorge (Biosystems Engineering, 2023)

An ƐHf and ẟ18O isotopic study of zircon of the Mount Osceola and Conway Granites, White Mountain Batholith, New Hampshire: Deciphering the petrogenesis of A-type granites - Javier F. Matos; Sean Kinney; Michael J. Dorais; Eric H. Christiansen (Lithos, 2023)

Geographic patterns of tree dispersal modes in Amazonia and their ecological correlates - Diego F. Correa; Pablo R. Stevenson; Maria Natalia Umaña; Luiz de Souza Coelho; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Iêda Leão do Amaral; Florian Wittmann; Francisca Dionízia de Almeida Matos; Carolina V. Castilho; Oliver L. Phillips; Juan Ernesto Guevara; et al. (Global Ecology and Biogeography, 2023)
Aim To investigate the geographic patterns and ecological correlates in the geographic distribution of the most common tree dispersal modes in Amazonia (endozoochory, synzoochory, anemochory and hydrochory). We examined if the proportional abundance of these dispersal modes could be explained by the availability of dispersal agents (disperser‐availability hypothesis) and/or the availability of resources for constructing zoochorous fruits (resource‐availability hypothesis). Time period Tree‐inventory plots established between 1934 and 2019. Major taxa studied Trees with a diameter at breast height (DBH) ≥ 9.55 cm. Location Amazonia, here defined as the lowland rain forests of the Amazon River basin and the Guiana Shield. Methods We assigned dispersal modes to a total of 5433 species and morphospecies within 1877 tree‐inventory plots across terra‐firme, seasonally flooded, and permanently flooded forests. We investigated geographic patterns in the proportional abundance of dispersal modes. We performed an abundance‐weighted mean pairwise distance (MPD) test and fit generalized linear models (GLMs) to explain the geographic distribution of dispersal modes. Results Anemochory was significantly, positively associated with mean annual wind speed, and hydrochory was significantly higher in flooded forests. Dispersal modes did not consistently show significant associations with the availability of resources for constructing zoochorous fruits. A lower dissimilarity in dispersal modes, resulting from a higher dominance of endozoochory, occurred in terra‐firme forests (excluding podzols) compared to flooded forests. Main conclusions The disperser‐availability hypothesis was well supported for abiotic dispersal modes (anemochory and hydrochory). The availability of resources for constructing zoochorous fruits seems an unlikely explanation for the distribution of dispersal modes in Amazonia. The association between frugivores and the proportional abundance of zoochory requires further research, as tree recruitment not only depends on dispersal vectors but also on conditions that favour or limit seedling recruitment across forest types.

Environmental disaster in mining areas: routes of exposure to metals in the Doce River basin - A. R. de Matos; H. T. da Silva; M. C. S. da Faria; B. M. Freire; R. M. Pereira; B. L. Batista; J. L. Rodrigues (International Journal of Environmental Science and Technology, 2022)

Lithology identification in carbonate thin section images of the Brazilian pre-salt reservoirs by the computational vision and deep learning - E. L. Faria; Juliana. M. Coelho; Thais F. Matos; Bernardo C. C. Santos; Willian A. Trevizan; J. L. Gonzalez; Clécio R. Bom; Márcio P. de Albuquerque; Marcelo P. de Albuquerque (Computational Geosciences, 2022)

A comprehensive ethnobotanical profile of Ocimum campechianum (Lamiaceae): from traditional medicine to phytochemical and pharmacological evidences - Estela Guardado Yordi; Maria J. Matos; Piergiacomo Buso; Amaury Pérez Martínez; Mercedes Asanza; Laura Scalvenzi; Stefano Manfredini; Massimo Tacchini; Matteo Radice; Gianni Sacchetti (Plant Biosystems, 2022)

Sexual segregation in the foraging distribution, behaviour, and trophic niche of the endemic Boyd’s shearwater (Puffinus lherminieri boydi) - Ivo dos Santos; Jaime A. Ramos; Filipe R. Ceia; Isabel Rodrigues; Nathalie Almeida; Stefan Antunes; Ana R. Carreiro; Diana M. Matos; Ricardo J. Lopes; Pedro Geraldes; Vítor H. Paiva (Marine Biology, 2022)

Treatment of Wastewater Containing New and Non-biodegradable Textile Dyes: Efficacy of Combined Advanced Oxidation and Adsorption Processes - Ana J. Feuzer-Matos; Renan C. Testolin; Wendell Pimentel-Almeida; Ramaiana Radetski-Silva; Maria J. Deomar-Simões; Letícia Poyer-Radetski; Rafael Ariente-Neto; Marina J. Batista-Barwinski; Cleder A. Somensi; Claudemir M. Radetski (Water, Air, & Soil Pollution, 2022)

Pleurotus strains with remediation potential to remove toxic metals from Doce River contaminated by Samarco dam mine - M. P. O. Santos; M. V. N. Santos; R. S. Matos; A. S. Van Der Maas; M. C. S. Faria; B. L. Batista; J. L. Rodrigues; C. A. Bomfeti (International Journal of Environmental Science and Technology, 2022)

MAMMALS IN PORTUGAL : A data set of terrestrial, volant, and marine mammal occurrences in P ortugal - Clara Grilo; Beatriz C. Afonso; Filipe Afonso; Marta Alexandre; Sara Aliácar; Ana Almeida; Ivan Prego Alonso; Francisco Álvares; Paulo Alves; Paulo Célio Alves; Pedro Alves; Anabela Amado; et al. (Ecology, 2022)
Mammals are threatened worldwide, with ~26% of all species being included in the IUCN threatened categories. This overall pattern is primarily associated with habitat loss or degradation, and human persecution for terrestrial mammals, and pollution, open net fishing, climate change, and prey depletion for marine mammals. Mammals play a key role in maintaining ecosystems functionality and resilience, and therefore information on their distribution is crucial to delineate and support conservation actions. MAMMALS IN PORTUGAL is a publicly available data set compiling unpublished georeferenced occurrence records of 92 terrestrial, volant, and marine mammals in mainland Portugal and archipelagos of the Azores and Madeira that includes 105,026 data entries between 1873 and 2021 (72% of the data occurring in 2000 and 2021). The methods used to collect the data were: live observations/captures (43%), sign surveys (35%), camera trapping (16%), bioacoustics surveys (4%) and radiotracking, and inquiries that represent less than 1% of the records. The data set includes 13 types of records: (1) burrows | soil mounds | tunnel, (2) capture, (3) colony, (4) dead animal | hair | skulls | jaws, (5) genetic confirmation, (6) inquiries, (7) observation of live animal (8), observation in shelters, (9) photo trapping | video, (10) predators diet | pellets | pine cones/nuts, (11) scat | track | ditch, (12) telemetry and (13) vocalization | echolocation. The spatial uncertainty of most records ranges between 0 and 100 m (76%). Rodentia ( n =31,573) has the highest number of records followed by Chiroptera ( n = 18,857), Carnivora ( n = 18,594), Lagomorpha ( n = 17,496), Cetartiodactyla ( n = 11,568) and Eulipotyphla ( n = 7008). The data set includes records of species classified by the IUCN as threatened (e.g., Oryctolagus cuniculus [ n = 12,159], Monachus monachus [ n = 1,512], and Lynx pardinus [ n = 197]). We believe that this data set may stimulate the publication of other European countries data sets that would certainly contribute to ecology and conservation‐related research, and therefore assisting on the development of more accurate and tailored conservation management strategies for each species. There are no copyright restrictions; please cite this data paper when the data are used in publications.

Latent effects of intertidal encapsulated development on juvenile fitness of the marine snail Acanthina monodon - L. P. Salas-Yanquin; N. P. Pinilla; A. S. Matos; J. A. Bűchner-Miranda; J. M. Navarro; V. M. Cubillos; J. A. Pechenik; O. R. Chaparro (Marine Biology, 2022)

Transcriptome analysis reveals key defense-related genes upon SA induction in Cocos nucifera L. - C. Silverio-Gómez; J. Vega-Arreguín; G. Nic-Matos; M. Narváez-Cab; L. Sáenz-Carbonell; C. Oropeza (Genes & Genomics, 2022)

Production and bioaccessibility of Emiliania huxleyi biomass and bioactivity of its aqueous and ethanolic extracts - B. Vicente; J. Matos; R. Gomes; M. Sapatinha; Cláudia Afonso; T. Rodrigues; A. Amorim; N. M. Bandarra; Carlos Cardoso (Journal of Applied Phycology, 2021)

Sclerotium delphinii causing concentric leaf spots in Piper nigrum in Brazil - Robinson Severo; Leandro J. Soki Shibutani; Enayra S. Sousa; Kedma S. Matos; José Evando A. Beserra; Maruzanete P. de Melo (Australasian Plant Pathology, 2021)

Neurological disease caused by Oropouche virus in northern Brazil: should it be included in the scope of clinical neurological diseases? - Jannifer O. Chiang; Rafael S. Azevedo; Maria C. A. Justino; Haroldo J. Matos; Hideraldo L. S. Cabeça; Sandro P. Silva; Daniele F. Henriques; Eliana V. P. Silva; Gabriela S. S. Andrade; Pedro FC. Vasconcelos; Lívia C. Martins; Raimunda S. S. Azevedo (Journal of NeuroVirology, 2021)
We describe two neurological cases of Oropouche virus infection in northern Brazil, where the virus is endemic but neglected as a pathogen. This study reiterates the necessity of developing protocols for diagnosing infections and training medical personnel to recognize the pathogenicity of Oropouche virus in neurological infections.

The hidden curve behind COVID-19 outbreak: the impact of delay in treatment initiation in cancer patients and how to mitigate the additional risk of dying—the head and neck cancer model - Leandro L. Matos; Carlos Henrique Q. Forster; Gustavo N. Marta; Gilberto Castro Junior; John A. Ridge; Daisy Hirata; Adalberto Miranda-Filho; Ali Hosny; Alvaro Sanabria; Vincent Gregoire; Snehal G. Patel; Johannes J. Fagan; et al. (Cancer Causes & Control, 2021)

Bioactive and nutritional potential of Alaria esculenta and Saccharina latissima - C. Afonso; J. Matos; I. Guarda; A. Gomes-Bispo; R. Gomes; C. Cardoso; S. Gueifão; I. Delgado; I. Coelho; I. Castanheira; N. M. Bandarra (Journal of Applied Phycology, 2021)

Bemessungsbeispiele von Tosbecken unterhalb von Treppenschussrinnen - Ivan Stojnic; Michael Pfister; Jorge Matos; Giovanni De Cesare; Anton J. Schleiss (WASSERWIRTSCHAFT, 2021)

Treptacantha abies-marina (S.G. Gmelin) Kützing: Characterization and Application as a Whole Food Ingredient - C. Afonso; I. Guarda; M. Mourato; L.L. Martins; I. Fonseca; R. Gomes; J. Matos; A. Gomes; N.M. Bandarra; C. Cardoso (Journal of Aquatic Food Product Technology, 2020)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

The Aftermath of Hurricane María on Puerto Rican Small-Scale Fisheries - Juan J. Agar; Manoj Shivlani; Daniel Matos-Caraballo (Coastal Management, 2020)

Statistical accuracy for estimations of large wood blockage in a reservoir environment - Paloma Furlan; Michael Pfister; Jorge Matos; Conceição Amado; Anton J. Schleiss (Environmental Fluid Mechanics, 2020)

Commercial Red Seaweed in Portugal (Gelidium sesquipedale and Pterocladiella capillacea, Florideophyceae): Going beyond a Single-Purpose Product Approach by Valorizing Bioactivity - J. Matos; A. Gomes; C. Cardoso; C. Afonso; A. M. Campos; R. Gomes; P. Falé; Inês Delgado; Inês Coelho; Isabel Castanheira; N. M. Bandarra (Thalassas: An International Journal of Marine Sciences, 2020)

Lipid composition and some bioactivities of 3 newly isolated microalgae (Tetraselmis sp. IMP3, Tetraselmis sp. CTP4, and Skeletonema sp.) - C. Cardoso; H. Pereira; J. Franca; J. Matos; I. Monteiro; P. Pousão-Ferreira; A. Gomes; L. Barreira; J. Varela; N. Neng; J. M. Nogueira; C. Afonso; et al. (Aquaculture International, 2020)

Modulation of P2Y2 receptors in bovine cumulus oocyte complexes: effects on intracellular calcium, zona hardening and developmental competence - E. Fonseca; P. Mesquita; C. C. Marques; M. C. Baptista; J. Pimenta; J. E. Matos; G. Soveral; R. M. L. N. Pereira (Purinergic Signalling, 2020)

A risk-based multi-level stress test methodology: application to six critical non-nuclear infrastructures in Europe - Sotirios A. Argyroudis; Stavroula Fotopoulou; Stella Karafagka; Kyriazis Pitilakis; Jacopo Selva; Ernesto Salzano; Anna Basco; Helen Crowley; Daniela Rodrigues; José P. Matos; Anton J. Schleiss; Wim Courage; et al. (Natural Hazards, 2020)

Isotopes and geochemistry to assess shallow/thermal groundwater interaction in a karst/fissured-porous environment (Portugal): a review and reinterpretation - J. M. Marques; C. Matos; P. M. Carreira; M. O. Neves (Sustainable Water Resources Management, 2019)

Metal content in Mullus surmuletus in the Canary Islands (North-West African Atlantic) - Enrique Lozano-Bilbao; Raquel Viñé; Gonzalo Lozano; Arturo Hardisson; Carmen Rubio; Dailos González-Weller; Emiliano Matos-Perdomo; Ángel J. Gutiérrez (Environmental Science and Pollution Research, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Selection of oviposition sites by ground beetles Abaris basistriata and Selenophorus seriatoporus for mass rearing purposes - Crislany L. Barbosa-Andrade; Daniel J. Andrade; Sidnéia T. S. Matos; Luciano Nogueira; Francisco J. Cividanes (BioControl, 2019)

40Ar-39Ar dating of Archean iron oxide Cu-Au and Paleoproterozoic granite-related Cu-Au deposits in the Carajás Mineral Province, Brazil: implications for genetic models - Peter J. Pollard; Roger G. Taylor; Lisa Peters; Fernando Matos; Cantidiano Freitas; Lineu Saboia; Sergio Huhn (Mineralium Deposita, 2019)

Effect of temperature on the thermal conductivity of a granite with high heat production from Central Portugal - M. M. Miranda; C. R. Matos; N. V. Rodrigues; A. J. S. C. Pereira; J. J. Costa (Journal of Iberian Geology, 2019)

Efficient biotechnological synthesis of flavor esters using a low-cost biocatalyst with immobilized Rhizomucor miehei lipase - Ulisses M. F. de Oliveira; Leonardo J. B. Lima de Matos; Maria Cristiane M. de Souza; Bruna B. Pinheiro; José C. S. dos Santos; Luciana R. B. Gonçalves (Molecular Biology Reports, 2019)

Pre-hatching development in the intertidal zone negatively affects juvenile survival and physiology in the muricid gastropod Acanthina monodon - O. R. Chaparro; L. P. Salas-Yanquin; A. S. Matos; J. A. Bűchner-Miranda; M. W. Gray; V. M. Cubillos; J. A. Pechenik (Marine Biology, 2018)

Taxon cycle predictions supported by model‐based inference in Indo‐Pacific trap‐jaw ants (Hymenoptera: Formicidae: Odontomachus ) - Pável Matos‐Maraví; Nicholas J. Matzke; Fredrick J. Larabee; Ronald M. Clouse; Ward C. Wheeler; Daniela Magdalena Sorger; Andrew V. Suarez; Milan Janda (Molecular Ecology, 2018)
Nonequilibrium dynamics and non‐neutral processes, such as trait‐dependent dispersal, are often missing from quantitative island biogeography models despite their potential explanatory value. One of the most influential nonequilibrium models is the taxon cycle, but it has been difficult to test its validity as a general biogeographical framework. Here, we test predictions of the taxon cycle model using six expected phylogenetic patterns and a time‐calibrated phylogeny of Indo‐Pacific Odontomachus (Hymenoptera: Formicidae: Ponerinae), one of the ant genera that E.O. Wilson used when first proposing the hypothesis. We used model‐based inference and a newly developed trait‐dependent dispersal model to jointly estimate ancestral biogeography, ecology (habitat preferences for forest interiors, vs. “marginal” habitats, such as savannahs, shorelines, disturbed areas) and the linkage between ecology and dispersal rates. We found strong evidence that habitat shifts from forest interior to open and disturbed habitats increased macroevolutionary dispersal rate. In addition, lineages occupying open and disturbed habitats can give rise to both island endemics re‐occupying only forest interiors and taxa that re‐expand geographical ranges. The phylogenetic predictions outlined in this study can be used in future work to evaluate the relative weights of neutral (e.g., geographical distance and area) and non‐neutral (e.g., trait‐dependent dispersal) processes in historical biogeography and community ecology.

Fos Protein as a Marker of Neuronal Activity: a Useful Tool in the Study of the Mechanism of Action of Natural Products with Analgesic Activity - Priscila L. Santos; Renan G. Brito; João Pedro S. C. F. Matos; Jullyana S. S. Quintans; Lucindo J. Quintans-Júnior (Molecular Neurobiology, 2018)

Towards Safer Data-Driven Forecasting of Extreme Streamflows - José P. Matos; Maria M. Portela; Anton J. Schleiss (Water Resources Management, 2018)

Integrated ecological–economic fisheries models—Evaluation, review and challenges for implementation - J Rasmus Nielsen; Eric Thunberg; Daniel S Holland; Jorn O Schmidt; Elizabeth A Fulton; Francois Bastardie; Andre E Punt; Icarus Allen; Heleen Bartelings; Michel Bertignac; Eckhard Bethke; Sieme Bossier; et al. (Fish and Fisheries, 2018)
Marine ecosystems evolve under many interconnected and area‐specific pressures. To fulfil society's intensifying and diversifying needs while ensuring ecologically sustainable development, more effective marine spatial planning and broader‐scope management of marine resources is necessary. Integrated ecological–economic fisheries models ( IEEFM s) of marine systems are needed to evaluate impacts and sustainability of potential management actions and understand, and anticipate ecological, economic and social dynamics at a range of scales from local to national and regional. To make these models most effective, it is important to determine how model characteristics and methods of communicating results influence the model implementation, the nature of the advice that can be provided and the impact on decisions taken by managers. This article presents a global review and comparative evaluation of 35 IEEFM s applied to marine fisheries and marine ecosystem resources to identify the characteristics that determine their usefulness, effectiveness and implementation. The focus is on fully integrated models that allow for feedbacks between ecological and human processes although not all the models reviewed achieve that. Modellers must invest more time to make models user friendly and to participate in management fora where models and model results can be explained and discussed. Such involvement is beneficial to all parties, leading to improvement of mo‐dels and more effective implementation of advice, but demands substantial resources which must be built into the governance process. It takes time to develop effective processes for using IEEFM s requiring a long‐term commitment to integrating multidisciplinary modelling advice into management decision‐making.

Importance of tissue sampling, laboratory methods, and patient characteristics for detection of Pneumocystis in autopsied lungs of non-immunosuppressed individuals - S. L. Vargas; C. Ponce; R. Bustamante; E. Calderón; G. Nevez; Y. De Armas; O. Matos; R. F. Miller; M. J. Gallo (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Increasing the Bile Acid Sequestration Performance of Cationic Hydrogels by Using an Advanced/Controlled Polymerization Technique - Patrícia V. Mendonça; André Matos; Andreia F. Sousa; Arménio C. Serra; Sérgio Simões; Jorge F. J. Coelho (Pharmaceutical Research, 2017)

Green zero-valent iron nanoparticles for the degradation of amoxicillin - S. Machado; J. G. Pacheco; H. P. A. Nouws; J. T. Albergaria; C. Delerue-Matos (International Journal of Environmental Science and Technology, 2017)

Peripheral and central antinociceptive effects of the butanolic fraction of Byrsonima verbascifolia leaves on nociception-induced models in mice - A. A. Saldanha; J. M. Siqueira; A. H. F. Castro; N. A. Matos; A. Klein; D. B. Silva; C. A. Carollo; A. C. Soares (Inflammopharmacology, 2017)

Variation in stem mortality rates determines patterns of above‐ground biomass in A mazonian forests: implications for dynamic global vegetation models - Michelle O. Johnson; David Galbraith; Manuel Gloor; Hannes De Deurwaerder; Matthieu Guimberteau; Anja Rammig; Kirsten Thonicke; Hans Verbeeck; Celso von Randow; Abel Monteagudo; Oliver L. Phillips; Roel J. W. Brienen; et al. (Global Change Biology, 2016)
Understanding the processes that determine above‐ground biomass ( AGB ) in Amazonian forests is important for predicting the sensitivity of these ecosystems to environmental change and for designing and evaluating dynamic global vegetation models ( DGVM s). AGB is determined by inputs from woody productivity [woody net primary productivity ( NPP )] and the rate at which carbon is lost through tree mortality. Here, we test whether two direct metrics of tree mortality (the absolute rate of woody biomass loss and the rate of stem mortality) and/or woody NPP , control variation in AGB among 167 plots in intact forest across Amazonia. We then compare these relationships and the observed variation in AGB and woody NPP with the predictions of four DGVM s. The observations show that stem mortality rates, rather than absolute rates of woody biomass loss, are the most important predictor of AGB , which is consistent with the importance of stand size structure for determining spatial variation in AGB . The relationship between stem mortality rates and AGB varies among different regions of Amazonia, indicating that variation in wood density and height/diameter relationships also influences AGB . In contrast to previous findings, we find that woody NPP is not correlated with stem mortality rates and is weakly positively correlated with AGB . Across the four models, basin‐wide average AGB is similar to the mean of the observations. However, the models consistently overestimate woody NPP and poorly represent the spatial patterns of both AGB and woody NPP estimated using plot data. In marked contrast to the observations, DGVM s typically show strong positive relationships between woody NPP and AGB . Resolving these differences will require incorporating forest size structure, mechanistic models of stem mortality and variation in functional composition in DGVM s.

Potential for CSO treatment with horizontal flow constructed wetlands: influence of hydraulic load, plant presence and loading frequency - J. Pisoeiro; A. Galvão; F. Ferreira; J. Matos (Environmental Science and Pollution Research, 2016)

Adaptive Gene Loss? Tracing Back the Pseudogenization of the Rabbit CCL8 Chemokine - Wessel van der Loo; Maria João Magalhaes; Ana Lemos de Matos; Joana Abrantes; Fumio Yamada; Pedro J. Esteves (Journal of Molecular Evolution, 2016)

Cometabolic Degradation of Anti-Inflammatory and Analgesic Pharmaceuticals by a Pentane Enrichment Culture - I. Bragança; A. S. Danko; J. Pacheco; D. Frascari; C. Delerue-Matos; V. F. Domingues (Water, Air, & Soil Pollution, 2016)

Riparian ecosystem configuration influences mesocarnivores presence in Mediterranean landscapes - Maria J. Santos; Luís M. Rosalino; Hugo M. Matos; Margarida Santos-Reis (European Journal of Wildlife Research, 2016)

Mucoadhesive nanoparticles: a new perspective for fish drug application - A C da S Costa; H M Brandão; S R da Silva; A R Bentes‐Sousa; J A P Diniz; J de J Viana Pinheiro; M de F C de Melo; J O C Silva; E R Matos; R M Ribeiro‐Costa (Journal of Fish Diseases, 2016)

Oral and endotracheal tubes colonization by periodontal bacteria: a case–control ICU study - A. N. Porto; S. C. Cortelli; A. H. Borges; F. Z. Matos; D. R. Aquino; T. B. Miranda; F. Oliveira Costa; A. F. Aranha; J. R. Cortelli (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Influence of Hydropower Development on Flow Regime in the Zambezi River Basin for Different Scenarios of Environmental Flows - T. Cohen Liechti; J. P. Matos; J.-L. Boillat; A. J. Schleiss (Water Resources Management, 2015)

New Thermoresistant Polymorph from CO2 Recrystallization of Minocycline Hydrochloride - Miguel A. Rodrigues; João M. Tiago; Luis Padrela; Henrique A. Matos; Teresa G. Nunes; Lídia Pinheiro; António J. Almeida; Edmundo Gomes de Azevedo (Pharmaceutical Research, 2014)

(1–3)-Beta-D-glucan in association with lactate dehydrogenase as biomarkers of Pneumocystis pneumonia (PcP) in HIV-infected patients - F. Esteves; C.-H. Lee; B. de Sousa; R. Badura; M. Seringa; C. Fernandes; J. F. Gaspar; F. Antunes; O. Matos (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Cu- and Zn-Soil Anomalies in the NE Border of the South Portuguese Zone (Iberian Variscides, Portugal) Identified by Multifractal and Geostatistical Analyses - F. Luz; A. Mateus; J. X. Matos; M. A. Gonçalves (Natural Resources Research, 2014)

Analysis of pesticide residues in strawberries and soils by GC-MS/MS, LC-MS/MS and two-dimensional GC-time-of-flight MS comparing organic and integrated pest management farming - Virgínia C. Fernandes; Steven J. Lehotay; Lucía Geis-Asteggiante; Hyeyoung Kwon; Hans G.J. Mol; Henk van der Kamp; Nuno Mateus; Valentina F. Domingues; Cristina Delerue-Matos (Food Additives & Contaminants: Part A, 2014)

Evolution of viral sensing RIG-I-like receptor genes in Leporidae genera Oryctolagus, Sylvilagus, and Lepus - Ana Lemos de Matos; Grant McFadden; Pedro J. Esteves (Immunogenetics, 2014)

Reproducibility of Positive Results for the Detection of Serum Galactomannan by Platelia™ Aspergillus EIA - Kelly C. M. C. Pedroza; Sócrates B. de Matos; Daniel L. de Moura; Mônica B. B. Oliveira; Marco A. S. Araújo; Roberto J. M. Nascimento; Fernanda W. M. Lima (Mycopathologia, 2013)

Geology of the Rosário–Neves Corvo antiform, Iberian Pyrite Belt, Portugal: new insights from physical volcanology, palynostratigraphy and isotope geochronology studies - J. T. Oliveira; C. J. P. Rosa; Z. Pereira; D. R. N. Rosa; J. X. Matos; C. M. C. Inverno; T. Andersen (Mineralium Deposita, 2013)

PAH air pollution at a Portuguese urban area: carcinogenic risks and sources identification - K. Slezakova; J. C. M. Pires; D. Castro; M. C. M. Alvim-Ferraz; C. Delerue-Matos; S. Morais; M. C. Pereira (Environmental Science and Pollution Research, 2013)

Delving into Delias Hübner (Lepidoptera: Pieridae): fine‐scale biogeography, phylogenetics and systematics of the world's largest butterfly genus - Chris J. Müller; Pável F. Matos‐Maraví; Luciano B. Beheregaray (Journal of Biogeography, 2013)
Aim Our objective was to reconstruct a species‐level phylogeny of the genus Delias , to elucidate their finer‐scale biogeography and to test boundaries between closely related taxa. Location Indo‐Australian region, with a focus on Wallacea. Methods Sequence data from 131 taxa, representing all recognized species groups and more than half of the known species of Delias , were used in the analysis. Phylogenetic analyses based on molecular characters of the mitochondrial gene cytochrome c oxidase subunit I ( COI ) and nuclear genes wingless and elongation factor 1α ( EF‐1α ) were carried out using maximum parsimony and Bayesian inference. Biogeographical reconstructions were undertaken using the parsimony‐based method dispersal–vicariance analysis and the dispersal–extinction–cladogenesis model as implemented in rasp and Lagrange , respectively. Results The phylogenetic hypothesis resolved 14 distinct clades, here designated the nysa , isse , pasithoe , belladonna , ladas , geraldina , aroae , eichhorni , sagessa , aganippe , hyparete , belisama , albertisi and nigrina species groups. Delias blanca Felder and Delias chrysomelaena Snellen van Vollenhoven were transferred to the pasithoe and isse species groups, respectively. We demonstrate that the barcode region of COI is useful for the delineation of closely related, more recently diverged, Delias species. Species diversification in Delias , for the most part, is shown to pre‐date the Pleistocene, even in montane mainland New Guinea where numerous phenotypically similar sister species co‐occur. Main conclusions Sibling Delias species found in sympatry are largely restricted to those clades confined to mainland New Guinea, where most species occur in high‐elevation habitats. Conversely, clades with large geographical ranges are composed of essentially allopatric taxa. Although an Australian Plate origin is plausible for the genus, Delias is likely to have colonized islands peripheral to Australia during the early stages of its evolution (i.e. during the Miocene), as evidenced by the presence of older lineages in Wallacea and also in islands of the south‐western Pacific.

Chloroplast SSR genetic diversity indicates a refuge for Corylus avellana in northern Portugal - S. Martins; F. Simões; D. Mendonça; J. Matos; A. P. Silva; V. Carnide (Genetic Resources and Crop Evolution, 2013)

Residual dopamine receptor desensitization following either high- or low-dose sub-chronic prior exposure to the atypical anti-psychotic drug olanzapine - Flávia Regina Cruz Dias; Liana Wermelinger de Matos; Maria de Fátima dos Santos Sampaio; Robert J. Carey; Marinete Pinheiro Carrera (Psychopharmacology, 2013)

Interleukin-6 gene −174G>C and −636G>C promoter polymorphisms and prostate cancer risk - J. F. Magalhães; A. J. Cortinhas; C. M. Albuquerque; C. S. Baptista; R. Ribeiro; Carlos Viegas; Augusto Matos; João Machado; Maria A. Pires; Henrique Guedes-Pinto; A. Martins-Bessa; J. C. Leitão; et al. (Molecular Biology Reports, 2013)

Influence of Catalyses on the Preparation of YVO4:Eu3+ Phosphors by the Sol–gel Methodology - Michelle Saltarelli; Priscilla P. Luz; Marcela G. Matos; Emerson H. de Faria; Katia J. Ciuffi; Paulo S. Calefi; Lucas A. Rocha; Eduardo J. Nassar (Journal of Fluorescence, 2012)

Diet and the risk of head and neck cancer: a pooled analysis in the INHANCE consortium - Shu-Chun Chuang; Mazda Jenab; Julia E. Heck; Cristina Bosetti; Renato Talamini; Keitaro Matsuo; Xavier Castellsague; Silvia Franceschi; Rolando Herrero; Deborah M. Winn; Carlo La Vecchia; Hal Morgenstern; et al. (Cancer Causes & Control, 2012)

A signature of six genes highlights defects on cell growth and specific metabolic pathways in murine and human hepatocellular carcinoma - Paul C. Schröder; Víctor Segura; José Ignacio Riezu; Bruno Sangro; José M. Mato; Jesús Prieto; Enrique Santamaría; Fernando J. Corrales (Functional & Integrative Genomics, 2011)

Alcohol and tobacco, and the risk of cancers of the upper aerodigestive tract in Latin America: a case–control study - K. Szymańska; R. J. Hung; V. Wünsch-Filho; J. Eluf-Neto; M. P. Curado; S. Koifman; E. Matos; A. Menezes; L. Fernandez; A. W. Daudt; P. Boffetta; P. Brennan (Cancer Causes & Control, 2011)

Drinking of maté and the risk of cancers of the upper aerodigestive tract in Latin America: a case–control study - K. Szymańska; E. Matos; R. J. Hung; V. Wünsch-Filho; J. Eluf-Neto; A. Menezes; A. W. Daudt; P. Brennan; P. Boffetta (Cancer Causes & Control, 2010)

An anti-inflammatory lectin from Luetzelburgia auriculata seeds inhibits adhesion and rolling of leukocytes and modulates histamine and PGE2 action in acute inflammation models - N. M. N. Alencar; R. S. B. Oliveira; J. G. Figueiredo; I. J. M. Cavalcante; M. P. V. Matos; F. Q. Cunha; J. V. S. Nunes; L. R. Bomfim; M. V. Ramos (Inflammation Research, 2010)

Scaleprinting: individual identification based on scale patterns - M. Morgado‐Santos; I. Matos; L. Vicente; M. J. Collares‐Pereira (Journal of Fish Biology, 2010)
A non‐intrusive method for individual identification of Iberian cyprinid complex Squalius alburnoides is presented, with possible application to other fish complexes and species. The proposed methodology is based on scale patterns that vary greatly between individuals.

Liver Histopathology in Brown Trout (Salmo trutta f. fario) from the Tinhela River, Subjected to Mine Drainage from the Abandoned Jales Mine (Portugal) - J. Carrola; A. Fontaínhas-Fernandes; P. Matos; E. Rocha (Bulletin of Environmental Contamination and Toxicology, 2009)

Impact of Acid Mine Drainage (AMD) on Water Quality, Stream Sediments and Periphytic Diatom Communities in the Surrounding Streams of Aljustrel Mining Area (Portugal) - A. T. Luís; P. Teixeira; S. F. P. Almeida; L. Ector; J. X. Matos; E. A. Ferreira da Silva (Water, Air, & Soil Pollution, 2009)

Dual augmentation for aerobic bioremediation of MTBE and TCE pollution in heavy metal-contaminated soil - V. C. Fernandes; J. T. Albergaria; T. Oliva-Teles; C. Delerue-Matos; P. De Marco (Biodegradation, 2009)

Variable number tandem repeat loci providing discrimination within widespread genotypes of Acinetobacter baumannii - J. F. Turton; J. Matos; M. E. Kaufmann; T. L. Pitt (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

Bulk adhesive strength of recombinant hybrid mussel adhesive protein - Hyung Joon Cha; Dong Soo Hwang; Seonghye Lim; James D. White; Cristina R. Matos-Perez; Jonathan J. Wilker (Biofouling, 2009)

Genetic characterization of the UCS and Kex1 loci of Pneumocystis jirovecii - F. Esteves; A. Tavares; M. C. Costa; J. Gaspar; F. Antunes; O. Matos (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

Does riparian habitat condition influence mammalian carnivore abundance in Mediterranean ecosystems? - Hugo M. Matos; Maria J. Santos; Francisco Palomares; Margarida Santos-Reis (Biodiversity and Conservation, 2009)

Assessing dam implementation impact on threatened carnivores: the case of Alqueva in SE Portugal - Maria J. Santos; Nuno M. Pedroso; Joaquim P. Ferreira; Hugo M. Matos; Teresa Sales-Luís; Íris Pereira; Carla Baltazar; Clara Grilo; Ana T. Cândido; Inês Sousa; Margarida Santos-Reis (Environmental Monitoring and Assessment, 2008)

Distal colonic Na+ absorption inhibited by luminal P2Y2 receptors - J. E. Matos; M. V. Sorensen; C. S. Geyti; B. Robaye; J. M. Boeynaems; J. Leipziger (Pflügers Archiv - European Journal of Physiology, 2007)

Effects of Cu, Ni and Zn on Lettuce Grown in Metal-Enriched Vermicompost Amended Soil - C. P. Jordão; L. L. Fialho; P. R. Cecon; A. T. Matos; J. C. L. Neves; E. S. Mendonça; R. L. F. Fontes (Water, Air, & Soil Pollution, 2006)

Assessment of Water Systems for Contaminants from Domestic and Industrial Sewages - C. P. Jordão; M. G. Pereira; C. R. Bellato; J. L. Pereira; A. T. Matos (Environmental Monitoring and Assessment, 2002)

Effects of pH and Dose on Nasal Absorption of Scopolamine Hydrobromide in Human Subjects - Shamim Ahmed; Anthony P. Sileno; Jorge C. deMeireles; Ramneik Dua; Harish K. Pimplaskar; Wei J. Xia; John Marinaro; Edward Langenback; Frank J. Matos; Lakshmi Putcha; Vincent D. Romeo; Charan R. Behl (Pharmaceutical Research, 2000)

Geology and geophysics as successful tools in the discovery of the Lagoa Salgada Orebody (Sado Tertiary Basin - Iberian Pyrite Belt), Grndola, Portugal - V. Oliveira; J. Matos; M. Bengala; N. Silva; P. Sousa; L. Torres (Mineralium Deposita, 1997)